Depression and Anxiety Incidence During Pregnancy Between Bariatric Surgery Patients and Matched Control Subjects - Kim, Jaewhan; Kelley, Joshua; Davidson, Lance; Richards, Nathan; Adams, Ted (Obesity surgery, 2022)
Purpose Obesity is a well-known risk factor for depression and mental illnesses. Metabolic and bariatric surgery (MBS) is a common treatment for individuals with severe obesity. Studies suggest that MBS is associated with increased risk of depression. However, little is known if pregnant women following MBS have greater incidence of depression/anxiety than non-surgical pregnant women with severe obesity. Materials and Methods Utah Bariatric Surgery Registry (UBSR) was used to identify subjects who underwent bariatric surgery between 1996 and 2016 and were matched (1:2 matching) to subjects with severe obesity from the Utah Population Database (UPDB). Depression and anxiety diagnoses during pregnancy were identified from birth records and electronic medical records (EMRs) during 10 months before birth. A multivariate logistic regression with clustering due to same subjects with multiple births was used. Results Patients included 1427 MBS women (associated 2492 births) and 2854 non-surgical women (associated 4984 births). In the surgical group, 24.4% of the pregnancies had diagnosed depression/anxiety, while 14.3% of the pregnancies in the control group had depression/anxiety ( p < 0.01). The surgery group had 1.51 times higher odds of depression and/or anxiety during pregnancy than the control group after controlling for covariates (OR = 1.51, p < 0.01). Conclusion The present study provides evidence that women who previously underwent MBS have higher odds of depression/anxiety during pregnancy than women with obesity who did not undergo MBS.